READING SKILLS TEST THROUGH BLOOM’S TAXONOMY - Nina Dwiastuty; Nurjanah Nurjanah (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2016)
AbstractThis paper aims to explain about various reading tests through Bloom’s Taxonomy. Reading test must involve three aspects, ; cognitive, affective and psychomotor. Cognitive task is about cognitive activity in understanding the text precisely and critically. Affective task is about the student’s willing and attitudes in reading, while psychomotor is about their activity in reading. The cognitive domain is divided into categories, begins from the lowest until the highest. Here they are the categories: firsty, remembering; Secondly, understanding; thirdly, applying; fourthly, analyzing; fifthly evaluating and sixthly creating. The test materials for reading skills should be considered by the degrees of difficulty, it is measured by its complexity vocabularies and structure; long – short text, the text given to students had better not too long; content, based on the student’s mental development, will, needs, or which attracts them and the genres. So, giving the reading test to the students is important to measure the student’s ability in understanding a text.Key words : reading test, Bloom’s Taxonomy, the reading materials test,AbstrakTulisan ini bertujuan untuk menjelaskan tentang macam-macam ujian membaca dengan menggunakan taxonomi Bloom . naskah bacaan meliputi tiga aspek yaitu kognitif, afektif, and pikomotor.Tugas kognitif adalah kegiatan kognitif dalam memahami naskah dengan tepat dan ktitis atau tentang kemampuan membaca mereka. Tugas afektif adalah keinginan siswa dalam menyikapi sebuah bacaan. Psikomotor adalah kegiatan mereka ketika sedang membaca. Pada domain kognitif dibagi menjadi beberapa tingkatan dimulai pada tingkat terendah sampai tertinggi, pertama mengingat, kedua memahami, ketiga menerapkan, keempat menganalisis, kelima mengevaluasi keenam menciptakan. Materi-materi ujian keterampilan membaca seharusnya ditinjau dari tingkat kesulitan diukur dengan kosakata dan struktur yang rumit; naskah panjang-pendek, diberikan kepada siswa tidak terlalu panjang; isi, mengenai perkembangan mental siswa, keinginan, keperluan; dan macam- macam jenis bacaan. Dengan demikian, memberikan ujian membaca kepada siswa sangat penting dilakukan untuk mengukur kemampuan siswa dalam memahami sebuah naskah.Kata Kunci: ujian membaca, Taxonomi Bloom, ujian materi- materi membaca